Analysis of the Influence of Novel Service Concept, Customer Satisfaction, and Novel Service Procedure on Customer Loyalty - Welly Surjono; Ahmad Johan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study was conducted to see the antecedents of customer loyalty by considering customer satisfaction and service innovation components, namely novel service concept and novel service procedure. The study was conducted on 208 users of streaming service applications such as Spotify, Netflix, Viu, Prime Video, HBO Go, and Disney+ Hotstar, who were selected using purposive sampling techniques with several criteria. Data were obtained from questionnaires distributed online using Google Forms, which were shared on social media of users of streaming service applications. The results of this study indicate that novel service concept, novel service procedure, and customer satisfaction have a positive effect on consumer loyalty. This study contributes to the literature on service innovation and customer loyalty in streaming services, while also providing suggestions for streaming service providers to improve customer retention.